Mechanism and prospects of mitochondrial transplantation for spinal cord injury treatment - Qin Wang; Xin Wang; Zhizhong Shang; Long Zhao (Stem Cell Research & Therapy)
Abstract Spinal cord injury (SCI) involves a continuous and dynamic cascade of complex reactions, with mitochondrial damage and dysfunction-induced energy metabolism disorders playing a central role throughout the process. These disorders not only determine the severity of secondary injuries but also influence the potential for axonal regeneration. Given the critical role of energy metabolism disturbances in the pathology of SCI, strategies such as enhancing mitochondrial transport within axons to alleviate local energy deficits, or transplanting autologous or allogeneic mitochondria to restore energy supply to damaged tissues, have emerged as potential approaches for SCI repair. These strategies also aim to modulate local inflammatory responses and apoptosis. Preclinical studies have initially demonstrated that mitochondrial transplantation (MT) significantly reduces neuronal death and promotes axonal regeneration following spinal cord injury. MT achieves this by regulating signaling pathways such as MAPK/ERK and PI3K/Akt, promoting the expression of growth-associated protein-43 (GAP-43) in neurons, and inhibiting the expression of apoptosis-related proteins like Grp78, Chop, and P-Akt, thereby enhancing the survival and regeneration of damaged neurons. Additionally, MT plays a role in promoting the expression of vascular endothelial growth factor, facilitating tissue repair, and reducing the secretion of pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6. Furthermore, MT modulates neuronal apoptosis and inflammatory responses by decreasing the expression of p-JNK, a member of the MAPK family. In summary, by reviewing the detailed mechanisms underlying the cascade of pathological processes in SCI, we emphasize the changes in endogenous mitochondria post-SCI and the potential of exogenous MT in SCI repair. This review aims to provide insights and a basis for developing more effective clinical treatments for SCI. Graphical abstract